Nutritional status and consumption of energy drinks among gym goers and non-gym-goers in Luanda, Angola - Lúcia de Fátima Chavito Massanga; Marli Stela Santana (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2024)
Energy drinks, also consisting of carbohydrates and sugars, are known for their stimulating effects, both in improving muscle performance and psychostimulating effects, especially among physical activity practitioners and young people. Thus, the study sought to understand the relationship between the nutritional status and the consumption of energy drinks in individuals attending gyms and non-attending gyms in Luanda, Angola, through the inclusion of 204 male individuals, 102 for each group. The results showed that the most consumed drinks were coffee and the national energy drink "A", with a statistically significant association between the variables Body Mass Index (BMI) and age, p=0.002 in FG and p=0.001 in non-gym-goers, and between BMI and the time of consumption of energy drinks (p=0.01) in gym-goers, demonstrating that such variables seem to tend to change the nutritional pattern of individuals.